Label-free identification and differentiation of different microplastics using phasor analysis of fluorescence lifetime imaging microscopy (FLIM)-generated data. (1st June 2021) - Monteleone, Adrian; Schary, Weronika; Wenzel, Folker; Langhals, Heinz; Dietrich, Daniel R.
Abstract: As plastic pollution is becoming an increasing worldwide problem, a variety of different techniques for the detection and in-depth characterization of plastics, including spectroscopy and chromatography methods, were introduced to the public. Recently we presented fluorescence lifetime imaging microscopy (FLIM) a new approach for the identification and characterization of microplastics using their fluorescence lifetime ( τ ) for differentiation. A very powerful extension of the recently established FLIM could be phasor analysis, which allows data representation in an interactive 2D graphical phasor plot thereby enabling a global view of the fluorescence decay in each pixel of the measured image. Microplastic particles generated from six different types of plastics were subjected to excitation wavelengths of 440 nm, upon which specific fluorescence lifetimes as well as the photon yield were determined using FLIM and phasor analysis. We could show that phasor analysis for FLIM with a laser pulse repetition frequency of 40 MHz was able to generate specific locations in the phasor plot for the plastics for fast differentiation, e.g. resulting in well-defined phasor plot positions for ABS at 3.019 ns, PPE at 6.239 ns, PET bottle from Germany at 2.703 ns and PET bottle from USA at 2.711 ns. Phasor analysis for FLIM proves to be a fast, label-free, and sensitive method for the identification and differentiation of plastics also with the aid of visualization variation enabling techniques such as heat treatment of plastics. Graphical abstract: Image 1 Highlights: Fast and fit-free analysis of fluorescence lifetimes of polymeric material. Useful for analysis of large datasets. Tool for representation of lifetime heterogeneity and differentiation of microplastic. Visualization and analysis of fluorescence lifetime variations through treatments (e.g. heat).